ENVIRONMENTAL CONSEQUENCES OF TRADITIONAL AGRICULTURE - Чайка, Т. О. (Scientific Progress & Innovations, 2013)
The article defines the need for a new understanding of the world on the principles of morality and ethical ideals of goodness and love. The necessity of the development of the agricultural sector on the basis of socio-economic-ecological system as a result of the negative impact of traditional agricultural production on the economy, the environment and the nation's population has been grounded. The consequences of the use of GMOs and GM crops in agriculture, which necessitates the development of organic agricultural production in Ukraine, are given in the article.